OPTIMALISASI PROSES DAN PERAN FORKOM PTNU (PRESPEKTIF MANAJEMEN DAN PENGEMBANGAN MASYARAKAT BANYUWANGI) - Rahman, Kholilur (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2021)
On Friday, February 25, 2021 PC NU Banyuwangi held a discussion event NU academics by inviting Rector of IAI Ibrahimy Genteng, Rector of IAI Darussalam Blokagung Karangdoro and Chairman of STAI Darul Ulum Sumberberas. The discussion decided the establishment of PTNU Banyuwangi Communication Forum as a forum for friendship of NU academics. This forum places the top level of management in its structure. Kh. Ahmad Munib Syafa'at, L.c., M.EI. (Rector of IAIDA) was appointed as the leader of the forum. This forum sets out the vision of